2016
DOI: 10.4085/1062-6050-51.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of National Collegiate Athletic Association Men's and Women's Cross-Country Injuries, 2009–2010 Through 2013–2014

Abstract: Context: Recent injury-surveillance data for collegiate-level cross-country athletes are limited.Objective: To describe the epidemiology of National Collegiate Athletic Association (NCAA) men's and women's crosscountry injuries during the 2009-2010 through 2013-2014 academic years.Design: Descriptive epidemiology study. Setting: Aggregate injury and exposure data collected from 25 men's and 22 women's cross-country programs, providing 47 and 43 seasons of data, respectively.Patients or Other Participants: Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 32 publications
3
40
3
4
Order By: Relevance
“…In studies using recent NCAA-ISP data, non-time-loss injuries comprised a range of 58.8% (women's cross country) to 77.2% (men's swimming and diving) of all reported injuries 24 25. These percentages of non-time-loss injuries are markedly higher than what we found in our investigation.…”
Section: Discussioncontrasting
confidence: 80%
“…In studies using recent NCAA-ISP data, non-time-loss injuries comprised a range of 58.8% (women's cross country) to 77.2% (men's swimming and diving) of all reported injuries 24 25. These percentages of non-time-loss injuries are markedly higher than what we found in our investigation.…”
Section: Discussioncontrasting
confidence: 80%
“…Running may be viewed as a healthy activity because it ultimately provides cardiometabolic benefits, but lower extremity musculoskeletal overuse injuries are very common in runners at various competitive levels [1,2]. Epidemiological data also demonstrate that running is the most frequent cause of exercise-and sport-related injuries in the military [3].…”
Section: Introductionmentioning
confidence: 97%
“…must also be considered as contributing to overall training load. A recent study by Kerr et al . found that the majority of injuries in collegiate cross‐country are of an overuse mechanism, which is often attributed to errors in cumulative load management.…”
Section: Discussionmentioning
confidence: 99%